Universal implement for the basic soil cultivation with replaceable working bodies for tractors of a thrust class 3,0 - S. L. Dyomshin; D. A. Cheremisinov; V. P. Ostal'tsev (Аграрная наука Евро-Северо-Востока, 2018)
For conditions of the European part of north-eastern Russia the technologies of crop cultivation based on the use of a combined system of basic soil cultivation are most effective economically. This system consists of alternating different types of nonmoldboard soil tillage and different depth plowing. For carrying out these operations by one universal implement for the basic soil cultivation plough-blade cultivators PPN-3-35/2-70 for tractors of class 14 kN and PPN-4(5)-35/3-70 for tractors of class 30 kN have been developed. Field tests of PPN-4(5) -35 / 3-70, conducted in 2015 in the conditions of the experimental field of the FARC North-East, showed that during the basic soil cultivation on the occupied fallow and crop remains the implement steadily sustains a working tillage width and adjusting depth. When plowing, the degree of soil crumbling is equal to 65% and 39%, respectively; during non-moldboard soil cultivation - 72% and 53%. The productivity at non-moldboard cultivation of middle loamy soil is 1.55 ha/h at the fuel rate of 17.2 kg/ha, when ploughing - 0.92 ha/h and 29.6 kg/ha. At the same time, the degree of crumbling when plowing compacted medium-loamy soil is insufficient for soil cultivation directly under the sowing of grain crops. To improve the quality of plowing it is proposed to carry it out together with disking the topsoil by equipping the universal implement with a disk section. To increase productivity, we also investigated the possibility of installing five plough bodies on the plough-blade cultivator PPN-4(5)-35/3-70 when aggregating it with T-150K tractor. In 2016 the agrotechnical assessment of the plough-blade cultivator PPN-4(5)-35/3-70 in the five-body version and with a disk section was carried out, which revealed that the universal implement performs plowing and plowing accompanied by disking in accordance with agrotechnical requirements, with the degree of soil crumbling by autumn plowing being 68.0%, by plowing with the upper soil layer cultivation 83.3%.